Public Narratives, Storytelling, and Trust: A Case Study in a STEM-Based Writing Program - Jeff Gagnon (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
In recent years, a growing body of scholars have argued that narrative storytelling is an effective and necessary science communication tool for the education of undergraduate STEM students. This research comes at a time when many in the public are becoming distrustful about science, scientists, and scientific communication. However, questions remain about which genre and style of narratives are most effective at building trust among STEM communicators and public audiences? My essay answers this question through a case study of narrative communication in my first-year writing classes. I analyze my attempts to teach STEM students that “public narratives,” a genre of writing created community organizer Marshall Ganz, represent a necessary intervention for bridging the larger communication gaps that are widening levels of distrust among scientists and science-skeptical publics across the country. As a unique genre of writing, public narratives combine personal storytelling with audience-driven connection and persuasive writing. They are founded on three communicative elements that undergraduate STEM students need significantly more knowledge and training in as they prepare to engage the public in their areas of professional specialization; these areas include storytelling their own experiences with skepticism and distrust, the rejection of condescension, labeling and dismissiveness, and a compassionate approach to listening and understanding audiences that seem skeptical or even opposed to science.